Intelligent innovation across disciplines: key trends from recent research in AI, IoT, and automation - Tole Sutikno (Institute of Advanced Engineering and Science, 2026)
The fast growth of artificial intelligence (AI), the Internet of Things (IoT), and automation is changing research and business in many fields. This issue has 76 new pieces of research that show new ways to use technology and new ways to accomplish things in healthcare, communication networks, smart energy, farming, and industrial automation. Deep learning and hybrid AI models improve disease identification, medical picture segmentation, and patient monitoring in healthcare, focusing on both accuracy and ease of understanding. In communication and the IoT, contributions include smart resource allocation for 5G and 6G networks, spectrum sensing, and cybersecurity frameworks that deal with efficiency, latency, and resilience in connected environments. AI and the IoT are important for sustainability and city planning. For example, smart energy management, predicting the weather in greenhouses, and using drones to monitor traffic are all examples of this. Also, the development of autonomous guided cars and Industry 5.0 automation shows how intelligent systems can be used in industrial operations. These works show how AI, IoT, and automation are coming together and how they could change the way people operate, make decisions, and solve problems in many fields. This issue shows how important it is to use ideas from many fields to drive the next generation of smart innovation